ANATOMY OF THE DARK SIDE OF GOVERNANCE:: BETWEEN FORMAL LEGALITY AND TRANSACTIONAL REALITY - Maisondra Maisondra; Fifian Adeningsi Mus (Institut Pemerintahan Dalam Negeri, 2026)
This research dissects the phenomenon of bureaucratic pathology in Indonesia through the concept of the